Unveiling the Hidden Patterns: A Dermoscopic Analysis of Vitiligo Lesions at a Tertiary Care Center in Surakarta, Indonesia - Sesia Pradestine; Muhammad Eko Irawanto; Osdatilla Esa Putri; Trya Oktaviani; Benedicta Lauda Anandita (HM Publisher, 2025)
Background: Vitiligo, a common depigmenting disorder, presents with a variety of clinical manifestations. Dermoscopy, a non-invasive skin imaging technique, has emerged as a valuable tool for evaluating pigmentary disorders. This study aimed to analyze the dermoscopic patterns of vitiligo lesions in a cohort of patients at a tertiary care center in Surakarta, Indonesia, and to correlate these patterns with disease stability. Methods: This cross-sectional study included 20 adult patients diagnosed with vitiligo at the Dermatology and Venereology Outpatient Clinic of Dr. Moewardi Regional General Hospital Surakarta in July 2023. A dermoscopic examination was performed on all patients using a polarized light dermoscope. Dermoscopic features were analyzed and categorized based on the BPLeFoSK criteria (Border, Pigment Network, Lesions, Follicular, Koebner). Disease stability was assessed based on clinical and dermoscopic findings. Results: The majority of patients were female (75%) and between 21-40 years old (65%). All patients exhibited the characteristic